The lie about the truck : Survivor, reality TV, and the endless gaze - Tisdale, Sallie (Gallery Books, 2021)
"In a world of fake news and rampant conspiracy theories, the nature of truth has increasingly blurry borders. In this clever and timely cultural commentary, award-winning author Sallie Tisdale tackles this issue by framing it in a familiar way-reality TV, particularly the long-running CBS show Survivor. With humor and in-depth superfan analysis, Tisdale explores the distinction between suspended disbelief and true authenticity both in how we watch shows like Survivor, and in how we perceive the world around us."--